Mixed Aggregates of the Dilithiated Koga Tetraamine: NMR Spectroscopic and Computational Studies. Issue 34 (20th July 2016) - Ma, Yun; Mack, Kyle A.; Liang, Jun; Keresztes, Ivan; Collum, David B.; Zakarian, Armen
Abstract: A combination of 1 H, 6 Li, 13 C, and 15 N NMR spectroscopies and density functional theory computations explores the formation of mixed aggregates by a dilithium salt of a C2 ‐symmetric chiral tetraamine (Koga's base). Lithium halides, acetylides, alkoxides, and monoalkylamides form isostructural trilithiated mixed aggregates with few exceptions. 6 Li– 13 C and 6 Li– 15 N couplings reveal heretofore undetected transannular contacts (laddering) with lithium acetylides and lithium monoalkylamides. Marked temperature‐dependent 15 N chemical shifts seem to be associated with this laddering. Computational studies shed light on the general structures of the aggregates, their penchant for laddering, and the stereochemical consequences of aggregation. Abstract : Koga's chiral dilithium amide used in asymmetric synthesis is shown to promiscuously form mixed aggregates with a wide variety of lithium salts including those containing halides, alkoxides, acetylides, and amides. Although largely isostructural, the presence or absence of Li−X transannular contacts distinguishes ladder from cyclic motifs.